The Effect of Neuroticism Level on Restrained Eaters’ Thinness Fantasy and Attentional Bias for Food - Kim, Jihyang; Kim, Kiho; Lee, Jang-Han (Frontiers in Psychology, 2019)
The aim of this study was to examine the role of restrained eaters’ neuroticism level in thinness fantasy and attentional bias for food following exposure to thin-ideal images. Eighty-five female participants were classified into four groups on the basis of their dietary restraint (restrained/unrestrained eaters) and neuroticism level (high/low). They completed self-reports (mood, body dissatisfaction level) on a visual analogue scale before and after exposure to thin-ideal images, and then their attentional bias for food was measured using eye-movements. Results indicated that after exposure to thin-ideal images, positive affect was more decreased in restrained eaters with high neuroticism compared to other groups and negative affect was increased in all groups except unrestrained eaters with low neuroticism. Also, restrained eaters with high neuroticism showed a heightened vigilance for food. These findings underscore the role of neuroticism in restrained eaters as a moderating factor of thinness fantasy.